Intellectual capital disclosure: annual report and website / Nik Anis Idayu Nik Abdullah - Nik Abdullah, Nik Anis Idayu (2013)
This study seeks to explore how companies in Malaysia disclose their intellectual capital (IC) information in the annual reports and websites. It examines the IC reporting practice of top 100 Malaysian companies based on market capitalization by analyzing IC disclosure both in annual reports and websites. This study also compares the annual reports and websites as medium of reporting IC information. In addition, this study analysed the association of various corporate governance mechanisms; board size, board composition, role duality, audit committee size and frequency of audit committee meeting with IC disclosure in both reporting mediums. The data was obtained from the annual reports for the year ended from 31 January 2011 to 31 December 2011 whereas data for companies’ websites were examined from 1 May to 31 May 2013. This study also employed a content analysis based on word count to determine the extent of IC disclosure in annual reports and websites. Inferential statistics were computed to examine the association between corporate governance mechanisms and IC disclosure. The study found that Malaysian companies disclosed more IC information in the annual report as compared to the websites. The analysis shows that none of the corporate governance variables have an association with IC disclosure both in annual reports and websites. This study would be of interest to accounting standard setters because it provides insight into the extensiveness of IC disclosure practices in Malaysia and also enhances their understanding on the need for framework for voluntary disclosures in the annual reports and websites.